The Chinese Smog Crisis as Media Event: Examining Twitter Discussion of the Documentary Under the Dome. Issue 4 (27th October 2018) - Lu, Shuning; Chen, Wenhong; Li, Xiaoqian; Zheng, Pei
Abstract : Media event theory examines how viewers take part in live televised events despite lack of physical presence. The media event scholarship has rarely considered how technologies like the Internet reconfigure the dynamics of such events. Drawing on Chinese language users' Twitter discussion about Under the Dome, a high‐profile 2015 documentary about air pollution in China, this article uses social network and content analyses to examine the mechanisms of media events in the networked digital space. Diverse actors engaged in the distribution and interpretation of this media event, most of whom were individual actors. Two subnetworks are revealed on Twitter: the disengaged one mainly distributed links to the documentary, and the engaged one actively discussed the documentary. While Twitter discussion of Under the Dome lacked broad and sophisticated discourse, we still find promising signs of public discussion on the smog issue and public policy in the long run. Theoretically, this study underscores the potential of integrating media event and framing theories to tackle the refashioned nature of media events. Empirically, the findings allow us to better understand how a wide range of individual and institutional actors co‐stage and co‐interpret media events by leveraging the technological and communicative affordances of Twitter.